Xanthogranulomatous Pyelonephritis: An Uncommon Form of Pyelonephritis Highlighted in a Case Report - Oliveira, Danielle Malavazi; Lacerda, Bárbara Sthefany de Paula; Hemerly, Matheus Compart; Santos, Maria Isabel Lima dos; Luchi , Weverton Machado (Brazilian Journal of Case Reports, 2024)
Xanthogranulomatous pyelonephritis is a rare and aggressive variant of pyelonephritis, characterized by chronic granulomatous inflammation that progresses to destruction of the renal parenchyma and renal failure. Early diagnosis is a challenge. We present the case of a 7-year-old girl with high fever, associated with low back pain, anorexia and vomiting for 30 days. After antibiotic therapy, radical nephrectomy was required for definitive treatment. Due to its rare and aggressive nature, which often leads to the loss of the affected kidney, it is essential to alert healthcare professionals about the importance of early diagnosis to prevent disease progression and improve the patient’s prognosis. We will use a case report to explore the clinical, radiological and pathological aspects related to xanthogranulomatous pyelonephritis.